The Mental Health Impact of COVID-19 Racial and Ethnic Discrimination Against Asian American and Pacific Islanders - Zhou, Sasha; Banawa, Rachel; Oh, Hans (Frontiers in Psychiatry, 2021)
Hate crimes against Asian American/ Pacific Islanders (AAPI) have surged in the United States during the COVID-19 pandemic to alarming new levels. We analyzed data from the Healthy Minds Study, and found that COVID-19 related racial/ethnic discrimination was associated with greater odds of having depression, anxiety, non-suicidal self-injury, binge drinking, and suicidal ideation among AAPI university students (N=1697). Findings suggest that the COVID-19 pandemic precipitated discrimination, which has been linked to mental health problems, calling for more preventive interventions to address the AAPI population, especially given their low rates of formal treatment utilization.